Structural, optical, electrical and low temperature thermoelectric properties of degenerate polycrystalline Cu7Se4 thin films. Issue 3 (18th November 2013) - Urmila, K. S.; Asokan, T. Namitha; Philip, R. R.; Ganesan, V.; Okram, G. S.; Pradeep, B.
<x xml:space="preserve">Abstract</x> Polycrystalline copper selenide thin films of composition Cu7Se4 with thickness of the order of 350 nm are deposited on glass substrates at a temperature of 498 ± 5 K and pressure of 10−5 mbar using reactive evaporation with high purity copper (99.999%) and selenium (99.99%) as the elemental starting materials. X‐ray diffraction (XRD) shows the formation of Cu7Se4 thin films. Structural parameters such as lattice constant, particle size, dislocation density, number of crystallites per unit area and strain in the film are evaluated. The surface morphology and composition of the film are studied using 2D and 3D atomic force microscopy (AFM) and energy dispersive analysis of X‐rays (EDAX), respectively. Hall effect measurement is done at room temperature to determine the conductivity type, carrier concentration, carrier mobility and Hall coefficient of the film. The carrier concentration of the film at room temperature is found to be nearly 1021 cm−3 suggesting that the prepared films are degenerate semiconductors. The films possess a direct allowed transition with an optical band gap of 2.25 eV. High reflectance and low transmittance of the film in the near‐infrared region – a behaviour, which is typical of degenerate semiconductors is related to its high electrical conductivity (∼103 Ω−1 cm−1). Temperature variation of thermoelectric power (TEP) and electrical conductivity also suggests degenerate semiconductor like behaviour of the film. The observed positive Seebeck coefficient indicates p‐type conduction mechanism. The data from the analyses of Hall measurements and TEP have been combined to evaluate important material parameters such as mean free path, relaxation time, Fermi energy and effective mass. Certain possible applications of the prepared film in various fields are also discussed.